The collaborative dream: the life cycle of knowledge co-production projects and the survival dilemma - Pedregal, Belén (2025)
In this paper we present and critically evaluate a participatory mapping project called the Map of Water Conflicts in Andalusia (Spain) led by researchers at the University of Seville from 2017 to 2019. According to the available literature, projects of this nature denote initial enthusiasm, followed by decline and abandonment within a period of approximately five years. At the crossroads of the Map’s disappearance, we critically analyze the project expectations and outcomes while addressing the challenges of sustaining co-production interest and validity over time.Our evaluation uses available information produced throughout the project to contrast the project’s officially defined goals and participant expectations with the project outcomes. The results are then discussed from a process-based perspective in relation to the lifecycle of boundary objects, with particular attention to the role of the researchers as influential actors in contributing to the generation, sustainability, and relevance of co-production projects.Three phases were identified in the project lifecycle, interpretive flexibility, standardization, and infrastructure creation, with critical transitional moments that challenge its sustainability and even pose a “survival dilemma” for the project. We conclude that to awaken from the “collaborative dream,” it is essential to consider the dynamic and conflictive nature of co-production projects and the ongoing self-examination within project teams. Goals and expected outcomes should be designed to align with the project’s transition through different stages, which are, in turn, determined by political-institutional contexts and specific power relations.